Correlation of Salivary Statherin and Calcium Levels with Dental Calculus Formation: A Preliminary Study - Deepak Gowda Sadashivappa Pateel; Shilpa Gunjal; Swarna Y. Math; Devarasa Giriyapura Murugeshappa; Sreejith Muraleedharan Nair (Hindawi Limited, 2017)
Background. Salivary constituents have a wide range of functions including oral calcium homeostasis. Salivary proteins such as statherin inhibit crystal growth of calcium phosphate in supersaturated solutions and interact with several oral bacteria to adsorb on hydroxyapatite. Concurrently, saliva, which is supersaturated with respect to calcium phosphates, is the driving force for plaque mineralization and formation of calculus. Thus, the aim of the present study was to estimate and correlate salivary statherin and calcium concentration to the dental calculus formation. Methods. A cross-sectional study was conducted to assess the relationship between salivary statherin, calcium, and dental calculus among 70 subjects, aged 20-55 years. Subjects were divided into 3 groups based on the calculus scores as interpreted by Calculus Index which was followed by collection of whole saliva using Super•SAL™. Salivary calcium levels were assessed by calorimetric method using Calcium Assay kit (Cayman Chemical, Michigan, USA) and statherin levels by using ELISA Kit (Cusabio Biotech). Results. Statherin levels showed a weak negative correlation with the calcium levels and with calculus formation. The mean salivary statherin and calcium concentration were found to be 0.96 μg/ml and 3.87 mg/ml, respectively. Salivary statherin levels differed significantly among the three groups (p<0.05). Conclusions. Our preliminary data indicates that statherin could possibly play a role in the formation of dental calculus.